Arthropod-Borne Viruses in Mauritania: A Literature Review - Abdallahi El Ghassem; Bedia Abdoullah; Jemila Deida; Mohamed Aly Ould Lemrabott; Mohamed Ouldabdallahi Moukah; Mohamed Salem Ould Ahmedou Salem; Sébastien Briolant; Leonardo K. Basco; Khyarhoum Ould Brahim; Ali Ould Mohamed Salem Boukhary (Pathogens, 2023)
During the past four decades, recurrent outbreaks of various arthropod-borne viruses have been reported in Mauritania. This review aims to consolidate the current knowledge on the epidemiology of the major arboviruses circulating in Mauritania. Online databases including PubMed and Web of Science were used to retrieve relevant published studies. The results showed that numerous arboviral outbreaks of variable magnitude occurred in almost all 13 regions of Mauritania, with Rift Valley fever (RVF), Crimean–Congo hemorrhagic fever (CCHF), and dengue (DEN) being the most common infections. Other arboviruses causing yellow fever (YF), chikungunya (CHIK), o’nyong-nyong (ONN), Semliki Forest (SF), West Nile fever (WNF), Bagaza (BAG), Wesselsbron (WSL), and Ngari (NRI) diseases have also been found circulating in humans and/or livestock in Mauritania. The average case fatality rates of CCHF and RVF were 28.7% and 21.1%, respectively. RVF outbreaks have often occurred after unusually heavy rainfalls, while CCHF epidemics have mostly been reported during the dry season. The central and southeastern regions of the country have carried the highest burden of RVF and CCHF. Sheep, cattle, and camels are the main animal reservoirs for the RVF and CCHF viruses. Culex antennatus and Cx. poicilipes mosquitoes and Hyalomma dromedarii, H. rufipes, and Rhipicephalus everesti ticks are the main vectors of these viruses. DEN outbreaks occurred mainly in the urban settings, including in Nouakchott, the capital city, and Aedes aegypti is likely the main mosquito vector. Therefore, there is a need to implement an integrated management strategy for the prevention and control of arboviral diseases based on sensitizing the high-risk occupational groups, such as slaughterhouse workers, shepherds, and butchers for zoonotic diseases, reinforcing vector surveillance and control, introducing rapid point-of-care diagnosis of arboviruses in high-risk areas, and improving the capacities to respond rapidly when the first signs of disease outbreak are identified.